Geology of the Kroonstad kimberlite cluster, South Africa - Howarth, Geoffrey H (Rhodes University, Faculty of Science, Department of Geology, 2010)
The Cretaceous (133Ma) Kroonstad Group II Kimberlite Cluster is located approximately 200km south west of Johannesburg on the Kaapvaal Craton. The cluster is made up of six kimberlite pipes and numerous other intrusive dike/sill bodies. Three of the pipes are analysed in this study, which includes the: Voorspoed, Lace (Crown) and Besterskraal North pipes. These pipes were emplaced at surface into the Karoo Supergroup, which is comprised of older sedimentary rocks (300-185Ma) overlain by flood basalts (185Ma). At depth the pipes have intruded the Transvaal (2100-2600Ma) and Ventersdorp (2700Ma) Supergroups, which are comprised dominantly of carbonates and various volcanic units respectively. The pipes have typical morphology of South African pipes with circular to sub-circular plan views and steep 82o pipe margins. The Voorspoed pipe is 12ha in size and is characterised by the presence of a large block of Karoo basalt approximately 6ha in size at the current land surface. This large basalt block extends to a maximum of 300m below the current land surface. The main Lace pipe is 2ha is size with a smaller (<0.5ha) satellite pipe approximately 50m to the west. No information is available on the morphology of the Besterskraal North pipe as it is sub-economic and no mining has occurred. Samples from the Besterskraal North pipe were collected from the De Beers archives. The Kroonstad Cluster has been subjected to approximately 1750m of erosion post-emplacement, which has been calculated by the analysis of the crustal xenoliths with the pipe infill. The hypabyssal kimberlite from the three pipes shows a gradational evolution in magma compositions, indicated by the mineralogy and geochemistry. The Lace pipe is the least evolved and has characteristics more similar to Group I kimberlites. The Voorspoed and Besterskraal North kimberlite are intermediately and highly evolved respectively. The gradational evolution is marked by an increase in SiO2 and Na2O contents. Furthermore the occurrence of abundant primary diopside, aegirine, sanidine, K-richterite and leucite indicates evolution of the magma. The root zones of the pipes are characterised by globular segregationary transitional kimberlite, which is interpreted to be hypabyssal and not the result of pyroclastic welding/agglutination. The hypabyssal transitional kimberlite (HKt) is characterised by incipient globular segregationary textures only and the typical tuffisitic transitional kimberlite (TKt) end member (Hetman et al. 2004) is not observed. The HKt contact with the overlying volcaniclastic kimberlite (VK) infill is sharp and not gradational. The presence of HKt in the satellite blind pipe at Lace further indicates that the distinct kimberlite rock type must be forming sub-volcanically. The HKt is distinctly different at the Voorspoed and Lace pipes, which is likely a result of differing compositions of the late stage magmatic liquid. Microlitic clinopyroxene is only observed at the Lace HKt and is interpreted to form as a result of both crustal xenolith contamination and CO2 degassing. Furthermore the HKt is intimately associated with contact breccias in the sidewall. The root zones of the Kroonstad pipes are interpreted to form through the development of a sub-volcanic embryonic pipe. The volcaniclastic kimberlite (VK) infill of the Kroonstad pipes is not typical of South African tuffisitic Class 1 kimberlite pipes. The VK at Voorspoed is characterised by numerous horizontally layered massive volcaniclastic kimberlite (MVK) units, which are interpreted to have formed in a deep open vent through primary pyroclastic deposition. MVK is the dominant rock type infilling the Voorspoed pipe, however numerous other minor units occur. Normally graded units are interpreted to form through gravitational collapse of the tuff ring. MVK units rich in Karoo basalt and/or Karoo sandstone are interpreted to form through gravitational sidewall failure deep within an open vent. Magmaclasts are interpreted to form in the HKt during the development of an embryonic pipe and therefore the term autolith or nucleated autolith may be applied. Debate on the validity of the term nucleated autolith is beyond this study and therefore the term nucleated magmaclast is used to refer to spherical magmaclasts in the VK. The emplacement of the Kroonstad pipes is particularly complex and is not similar to typical Class 1 tuffisitic kimberlites. However the initial stage of pipe emplacement is similar to typical South African kimberlites and is interpreted to be through the development of an embryonic pipe as described by Clement (1982). The vent clearing eruption is interpreted to be from the bottom up through the exsolution of juvenile volatiles and the pipe shape is controlled by the depth of the eruption (+/-2km) (Skinner, 2008). The initial embryonic pipe development and explosive eruption is similar to other South African kimberlites, however the vent is cleared and left open, which is typical of Class 2 Prairies type and Class 3 Lac de Gras type pipes. The latter vent infilling processes are similar to Class 3 kimberlites from Lac de Gras and are dominated at the current level by primary pyroclastic deposition.
Keywords: Geology -- South Africa -- Kroonstad; Kimberlite -- South Africa -- Kroonstad